Dampak Tarif Donald Trump Terhadap Perekonomian Indonesia - Andrew, Andrew; Aminnatus Shalihah, Aliffa; Muliyasari Kusno, Erlina; Dika Ardiana, Muhammad; Putri Handayani, Nadya; Megawati, Vita (Publikasi Indonesia, 2025)
The protectionist tariff policy imposed by President Donald Trump, particularly the 32% tariff targeting developing countries, has placed significant pressure on Indonesia’s economic stability. This study aims to examine the comprehensive impact of the policy and evaluate the effectiveness of the Indonesian government’s responses. A mixed-method approach was employed, with a focus on descriptive and inferential quantitative analysis. Secondary data were collected from official institutions such as Statistics Indonesia (BPS), Bank Indonesia, the World Trade Organization (WTO), and the International Monetary Fund (IMF) for the period of 2015–2024. Key indicators analyzed include GDP, trade balance, exchange rate, inflation, and foreign direct investment (FDI). Data were processed using statistical software such as SPSS and EViews. The findings reveal that Indonesia’s steel exports to the United States experienced a short-term surge following the tariff announcement, but the increase was not sustained. Meanwhile, the domestic industry faced heightened pressure from an influx of low-cost imported steel. Government responses—mainly diplomatic and tactical—proved insufficient to address core structural issues, such as the low added value of exports and overdependence on limited markets. The study concludes that long-term structural reform is essential to strengthen Indonesia’s industrial competitiveness and economic resilience. While this research is limited to secondary data and does not include micro-level firm analysis, it offers valuable insight for policymakers, industry stakeholders, and researchers in developing strategies to manage future global trade disruptions.